LITERATURE REVEIW : Intervensi Myofascial Release Dan Terapi Latihan Untuk Meningkatkan Kemampuan Fungsional Pada Pasien Osteoarthritis Lutut - Muhammad Lucky Wicaksono (2020)
Introduction: Osteoarthritis is a degenerative joint disease associated with cartilage joint damage that causes the process of degradation. Risk factors for missing osteoarthritis are age, sex, physical activity, obesity and genetics. Purpose: This study aims to examine the literature, journals, articles or research results with the topic Literature riview: Myofascial Release Interventions and Physiotherapi Exercise to improve Functional in Knee Osteoathritis patients. Methods: Search for sources of literature, journals, articles, research results in several databases such as Google Schoolar, Elsevier, PEDro, PubMed by using certain keywords in the 2012-202 period. From the literature search results obtained 5 articles that meet the criteria of source inclusion. The methodological quality review of 5 articles is satisfied with Scimago Journal & Country Rank (SJR). Results: After reviewing the literature as many as 5 articles showed myofascial release and effective physiotherapi exercise in improving functional activity in knee Osteoarthritis patients. Conclusion: Myofascial Release and Physiotherapi Exercise significantly increase in Functional Activity in Knee Osteoarthritis patients.